Faktor-Faktor yang Mempengaruhi Tingkat Akurasi Perkiraan Biaya pada Tahap Konstruksi Gedung di Pemerintahan Kota Sungai Penuh - Wahyudi, Boyke Heri; Peli, Martalius; Zaitul, Zaitul (Jurnal Talenta Sipil, 2025)
Inaccurate cost estimates in building construction projects are often a source of budget overruns that disrupt project efficiency, including in the Sungai Penuh City Government. Several projects, such as the construction of a community health center, PSC building, and health laboratory, show significant deviations between the planned budget and actual costs. This study aims to identify the main factors influencing the accuracy of cost estimates, determine the dominant factors at play, and analyze the combined impact of these factors on the overall quality of cost estimation. The method used is a quantitative approach through the distribution of questionnaires to parties involved in the project, including the Project Implementation Unit (PPK), contractors, consultants, and technical teams. Data analysis was conducted using Confirmatory Factor Analysis (CFA) and multiple linear regression with the assistance of SPSS 22. The results of the study revealed three significant main groups of factors, namely estimator competence, information availability, and cost estimation calculation quality. Among the three, estimator competence was the most dominant factor. The research instrument was found to be valid and reliable with KMO values > 0.5 and Cronbach’s Alpha > 0.6. The conclusions of this study emphasize the importance of enhancing estimator capacity through continuous training, providing accurate cost databases, and standardizing estimation procedures. These efforts are expected to promote budget efficiency and improve the overall success of government construction projects.